Auditory training program for individuals with post-lingual hearing impairment: a scoping review - Marhaban, Juliana Aminah; Rahmat, Sarah; Mohamed Zain, Nor Azrita; Arafat Dzulkarnain, Ahmad Aidil (IIUM Press, 2023)
Introduction: Auditory training (AT) is an important area in aural rehabilitation that benefits individuals with post-lingual hearing impairment using amplification devices. The main benefit in targeting the auditory training program is to increase the quality of life by holistically reducing the hearing-loss-induced deficits of function through a combination of sensory management, instruction, perceptual training, and counselling. It also stimulates a successful listening using a training stimulus that engage the process for the role of cognition in auditory training, specifically executive processes such as attention switching and updating of memory. Such approach will need a meaningful training program for users to be able to generalize them in everyday life. This study is aimed at reviewing auditory training program in literatures for individuals with post-lingual hearing impairment with respect to the designs and parameters. Methods: Pubmed, Science Direct, Scopus and Pro Quest (medical and health) databases were searched using English keywords; hearing loss, auditory training, hearing aids, cochlear implants, perceptual learning, aural rehabilitation, auditory rehabilitation, adult. Papers were selected from year 2013 to 2018 and papers from grey search were included if the paper has been quoted as important to learn further about AT program used in paper accepted from databases. 209 papers were identified from the databases. After removing duplications and screening of the inclusion criteria, a total of 24 papers were accepted; 21 papers from databases search and three papers from grey search. All selected papers were reviewed by four reviewers. This study adopted Preferred Reporting Items for Systematic Reviews and Meta-analysis extension for Scoping Review (PRISMA-ScR). Results: The results described 15 auditory training programs from 24 papers with each program has an exceptional design but shared practically the same parameters. The AT program designs includes; 1. sample size, 2. hearing status, 3. hearing devices, 4. hearing age, 5. measurement test, 6. training sequence, 7. training durations, 8. training frequency, 9. length of training, 10. location of training, 11. training delivery style; either computer based or face to face, with trainer or self-training and individual or group training, 12. findings and 13. retention effects. The parameters used in auditory training program contains; 1. training activities, 2. training theme, 3. communication strategies, 4. methods, 5. approaches, 6. mode, 7. auditory skills, 8. speech stimulus, 9. sound stimulus and 10. complexity of training. Conclusions: Auditory training program for individuals with post-lingual hearing impairment was described in specific designs? and parameters to achieve its goal. The finding of this study could be used as a general guideline to develop the content and structure of future auditory training program